2021
DOI: 10.3390/plants10081670
|View full text |Cite
|
Sign up to set email alerts
|

Ethephon-Induced Ethylene Enhances Starch Degradation and Sucrose Transport with an Interactive Abscisic Acid-Mediated Manner in Mature Leaves of Oilseed rape (Brassica napus L.)

Abstract: The leaf senescence process is characterized by the degradation of macromolecules in mature leaves and the remobilization of degradation products via phloem transport. The phytohormone ethylene mediates leaf senescence. This study aimed to investigate the ethephon-induced ethylene effects on starch degradation and sucrose remobilization through their interactive regulation with other hormones. Ethephon (2-chloroethylphosphonic acid) was used as an ethylene-generating agent. Endogenous hormonal status, carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Recently, Wang et al (2020) and Wongjunta et al (2021) observed that STS inhibited ET production in lotus leaves and orchid flowers by suppressing the expression of ACS and the activities of ACS and ACO enzymes. Moreover, ethephon-enhanced ET production, ACS and ACO expression, and ACS and ACO activities have also been reported in previous studies (Imsabai et al, 2010;Lee et al, 2021;Nascimento et al, 2021;Wongjunta et al, 2021). Taken together, these findings showed that ethephon completely prevented stem bending in the three different cultivars of snapdragon cut flowers and that STS significantly stimulated stem bending.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Wang et al (2020) and Wongjunta et al (2021) observed that STS inhibited ET production in lotus leaves and orchid flowers by suppressing the expression of ACS and the activities of ACS and ACO enzymes. Moreover, ethephon-enhanced ET production, ACS and ACO expression, and ACS and ACO activities have also been reported in previous studies (Imsabai et al, 2010;Lee et al, 2021;Nascimento et al, 2021;Wongjunta et al, 2021). Taken together, these findings showed that ethephon completely prevented stem bending in the three different cultivars of snapdragon cut flowers and that STS significantly stimulated stem bending.…”
Section: Discussionsupporting
confidence: 87%
“…The remobilization of N assimilates from source leaves is a crucial determinant for the production of the reproductive organs (sink), especially in B. napus, which has low nitrogen remobilization capacity, with less than 50% of nitrogen stored in source leaves used for seed filling [25,26]. Ethylene is the active signal compound involved in the senescence process of source leaves and in the sink development [2,11,12,14]. In this context, the present study emphasized the regulatory role of ethylene in protein degradation and amino acid transport in mature leaves (source) in relation to pod (sink) development in response to ethephon treatment at the early regenerative stage of B. napus.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the depression of chlorophyll a/b-binding protein (CAB) gene was remarked in 50 and 75 ppm ethephon-treated mature leaves (Figure 1C), leading to a decrease in total chlorophyll content (−37.9% compared with the control) at day 30 (Figure 3E). Numerous studies have shown that exogenous application of ethylene or ethylene releaser accelerates the leaf senescence process [3,12,13]. Ethylene has been shown to be involved in the organized cell dismantling process, which includes nucleic acid reduction, protein degradation [36,37], lipid degradation, peroxidation [38,39], and the activation of nutrients recycling from senescing leaves to the other organs [17,19].…”
Section: Ethephon-induced Ethylene-mediated Leaf Senescencementioning
confidence: 99%
See 2 more Smart Citations